Problem-based e-worksheet innovation to improve HOTS and decision-making skills in differentiated learning - Ayuni, Melania Sandri; Distrik, I Wayan; Suyatna, Agus (Indonesian Journal of Science and Mathematics Education, 2025)
Higher-order thinking skills (HOTS) and decision-making skills are essential competencies in physics learning. Therefore, innovative learning materials such as problem-based e-worksheets are required. This study aims to develop a problem-based e-worksheet for differentiated learning that meets the criteria of validity, practicality, and effectiveness in improving students’ HOTS and decision-making skills. The study employed a mixed-methods approach with a sequential exploratory design and a static pretest–posttest design. Preliminary research was conducted to identify differences in students’ abilities and learning styles as the basis for designing the e-worksheet. The development stage involved creating e-worksheets and teaching modules, followed by product validation and field testing. The field test involved 60 senior high school students in Bandar Lampung, selected using cluster random sampling. The results showed that the problem-based e-worksheet achieved very high validity, with content and construct validation scores of 4.69 and 4.82. The e-worksheet also demonstrated high practicality, with implementation rates exceeding 80% and positive student responses. Furthermore, it was effective in improving HOTS with an n-gain of 0.76 and decision-making skills with an n-gain of 0.83. These findings indicate that problem-based e-worksheets are effective learning media for strengthening students’ thinking and decision-making skills in physics learning.